Методологічні засади інтеграції взаємозамінності, стандартизації та технічних вимірювань у процесах сертифікації транспортних засобів - Поліщук, Дмитро Володимирович; Головіна, Олена Валентинівна; Холодний, Юрій Федорович; Алтухов, Петро Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У роботі розглянуто методологічні засади інтеграції взаємозамінності, стандартизації та метрології у процесах сертифікації транспортних засобів. Доведено, що їхнє об’єднання є критичне для типового затвердження та відповідності виробництва. На прикладах світового досвіду показано, що зростання регуляторної суворості прямо вимагає підвищення точності метрології та спроможності взаємозамінності, гарантуючи безпеку та якість продукції.

The article analyzes the methodological foundations for integrating interchangeability, standardization, and metrology within the vehicle certification processes. Global trends show that the increasing complexity of transport means requires a unified, scientifically grounded approach to conformity assessment. The study conceptualizes the interchangeability, standardization and metrology synergy: standardization establishes unified regulatory requirements; interchangeability defines the necessary dimensional tolerances; and metrology provides the quantifiable evidence (through testing and process capability analysis, that these requirements are met during both type approval and conformity of production. The research emphasizes the critical role of metrology as the instrumental basis for legal and technical validation, noting that unreliable measurements undermine the validity of conformity of production. Comparative analysis of international certification systems demonstrates that stricter regulatory demands, such as the "zero contact" requirement in autonomous braking systems, necessitate a direct increase in the precision of metrological control and the overall capability of manufacturing processes. Key recommendations focus on mandatory ISO/IEC 17025 accreditation and the necessity of correcting indices for gauge measurement errors to achieve true process capability.
Methodological basis for the integration of interchangeability, standardization, and technical measurements in the certification processes of transport vehicles
Keywords: сертифікація; взаємозамінність; стандартизація; метрологія; транспортні засоби; типове затвердження; відповідність виробництва; certification; interchangeability; standardization; metrology; vehicle; type approval; conformity of production